2016
DOI: 10.1016/j.jpainsymman.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Enhance Goals-of-Care Communication Between Heart Failure Patients and Heart Failure Providers

Abstract: Context Heart failure patients contend with a markedly impaired quality of life, experiencing emotional distress and severe physical discomfort that increases in frequency in the last months of life. Improving communication between patients and providers about goals of care has the potential to improve patient-provider communication and patient outcomes. Objectives To determine the effects of a goals-of-care (GoC) intervention compared to usual care on the number of GoC conversations, quality of communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 45 publications
3
59
0
3
Order By: Relevance
“…Their results suggested that providing a multidisciplinary team early in the disease trajectory of the patient had a small but positive effect on patient satisfaction with end-of-life care. Possible causes for the success of the study by Doorenboss et al 55 corresponded with factors found in other studies of higher effect sizes: (a) patients were educated by a nurse through a question prompt list before their appointment with the cardiologist, (b) the nurse helped patients identifying and clarifying their care wishes and (c) the clinician was trained in end-of-life communication skills and had an advanced awareness of the patient's care preferences.…”
Section: Characteristics Of Acp Interventionsmentioning
confidence: 53%
See 1 more Smart Citation
“…Their results suggested that providing a multidisciplinary team early in the disease trajectory of the patient had a small but positive effect on patient satisfaction with end-of-life care. Possible causes for the success of the study by Doorenboss et al 55 corresponded with factors found in other studies of higher effect sizes: (a) patients were educated by a nurse through a question prompt list before their appointment with the cardiologist, (b) the nurse helped patients identifying and clarifying their care wishes and (c) the clinician was trained in end-of-life communication skills and had an advanced awareness of the patient's care preferences.…”
Section: Characteristics Of Acp Interventionsmentioning
confidence: 53%
“…63 For example, the timing of offering ACP as an intervention in relation to the patient's disease trajectory varied in included studies. While most patients in the meta-analysis suffered from heart failure class III or IVof the New York Heart Association, ACP was initiated at different time points: during an admission to hospital, 58 after a recent hospitalization, 55 after a deterioration in the patient's health status 52 or before a routine clinic appointment with a cardiologist. 53 These findings on the timing of ACP agree with the published literature which cites a change or deterioration in the patient's condition, a routine clinical review or a change in a patient's personal circumstances such as moving into a care home as possible triggers for ACP.…”
Section: Causes Of Clinical Heterogeneitymentioning
confidence: 99%
“…Individuals with advanced heart failure face a 5-year mortality rate of 50% following diagnosis (Benjamin et al, 2018). Considering the high mortality rate, there is a growing body of evidence on the importance of goals for care conversations between individuals with advanced illness and their health care providers (Doorenbos, Levy, Curtis, & Dougherty, 2016). An understanding of an individual's wishes is a foundational cornerstone of personcentered care and an individual's perception of his/her illness has profound implications regarding goals of care and decisions regarding advanced treatment options, such as mechanical circulatory support, especially at the end of life.…”
Section: Story Circlesmentioning
confidence: 99%
“…28 Fortunately, trials of triggered palliative care integration for patients with heart failure have shown increased patient satisfaction with physician communication regarding goals of care. 29,30 The topic of initiating goals-of-care discussions with patients with end-stage liver disease (ESLD) was first raised by Larson and Curtis in 2006. 31 It has been observed that a focus on liver transplant status may interfere with providing palliative care.…”
Section: Technological Imperativementioning
confidence: 99%
“…32 Triggered goals-of-care conversations in other diseases have resulted in improved quality of life, patient-physician communication, and congruence between care delivered and patient preferences. 21,23,26,[28][29][30] We are unaware of investigations regarding the outcomes of triggered goals-of-care discussions in organ transplant candidates or recipients.…”
Section: Strategies For Discussing and Resolving The Organ Transplantmentioning
confidence: 99%